Linear growth and body mass index in pediatric patients with Cushing's disease or simple obesity. - Greening, J; Storr, H; McKenzie, SA; Davies, K; Martin, L; Grossman, AB; Savage, M (2006)
BACKGROUND: Increasing prevalence of childhood obesity has resulted in an accelerating rate of referrals of overweight patients to pediatric clinics for exclusion of endocrine or metabolic etiologies. The exclusion of Cushing's disease (CD) requires complex and potentially invasive investigations. OBJECTIVE: To evaluate the sensitivity of accurate measurements of height, weight and body mass index (BMI) in discriminating between simple obesity and CD. METHODS AND PATIENTS: Height, weight and BMI were measured at diagnosis in 25 patients with CD; 14 males, 11 females, mean age 12.9 yr (6.4-17.8) and 41 patients with simple obesity (SO), defined as BMI >2.0 SD; 20 males, 21 females, mean age 9.4 yr (3.5-15.6). RESULTS: Mean (+/-SE) BMI SDS in the CD patients was 2.41+/-0.5 and in the SO patients 3.71+/-1.3. Height SDS in the CD patients was -1.88+/-0.24 and in the SO patients 1.18+/-0.19 (p<0.05). The mean (+/-SE) BMI SDS to height SDS ratio was significantly decreased in the CD compared with the SO patients; -1.81+/-0.54 vs +0.90+/-1.17 (p<0.0001). CONCLUSIONS: Simple, accurate measurement of height and BMI SDS values provides a quick, and sensitive diagnostic discriminator in pediatric patients with CD or SO, thus potentially avoiding complex investigations.